What can we learn from critical, liberation, and decolonization community psychologists of the global South? - Francescato, Donata (Rivista di Psicologia Clinica - Open Access, 2024)
The first part of this article illustrates how democracies are in crisis in many European countries and in the United States. The second part describes three important theoretical and political contributions made by critical community psychologists, decolonization, and liberation community psychologists to find theoretical constructs and action strategies that could enrich mainstream European and North American Clinical and Community Psychology. The third part explores how a thousand clinical psychologists, especially family therapists worldwide, have, through the Assisi Manifest, denounced the increase in psychological problems worldwide and the need to work not only with families but in the communities where people live. The last part outlines the major theoretical constructs and intervention methodologies we can integrate into our European community psychology activities and how to transform our “community homes” to decrease polarization and foster dialogue to foster better capabilities to care for one another and solve local and planetary problems.